Emerging therapeutic strategies targeting extracellular histones for critical and inflammatory diseases: an updated narrative review - Yang, Tinghang; Peng, Jing; Zhang, Zhuyun; Chen, Yu; Liu, Zhihui; Jiang, Luojia; Jin, Lunqiang; Han, Mei; Su, Baihai; Li, Yupei (Frontiers in Immunology, 2024)
Extracellular histones are crucial damage-associated molecular patterns involved in the development and progression of multiple critical and inflammatory diseases, such as sepsis, pancreatitis, trauma, acute liver failure, acute respiratory distress syndrome, vasculitis and arthritis. During the past decade, the physiopathologic mechanisms of histone-mediated hyperinflammation, endothelial dysfunction, coagulation activation, neuroimmune injury and organ dysfunction in diseases have been systematically elucidated. Emerging preclinical evidence further shows that anti-histone strategies with either their neutralizers (heparin, heparinoids, nature plasma proteins, small anion molecules and nanomedicines, etc.) or extracorporeal blood purification techniques can significantly alleviate histone-induced deleterious effects, and thus improve the outcomes of histone-related critical and inflammatory animal models. However, a systemic evaluation of the efficacy and safety of these histone-targeting therapeutic strategies is currently lacking. In this review, we first update our latest understanding of the underlying molecular mechanisms of histone-induced hyperinflammation, endothelial dysfunction, coagulopathy, and organ dysfunction. Then, we summarize the latest advances in histone-targeting therapy strategies with heparin, anti-histone antibodies, histone-binding proteins or molecules, and histone-affinity hemoadsorption in pre-clinical studies. Finally, challenges and future perspectives for improving the clinical translation of histone-targeting therapeutic strategies are also discussed to promote better management of patients with histone-related diseases.